Measurement of laser differential confocal geometrical parameters for ICF capsule - Longxiao Wang; Yun Wang; Xianxian Ma; Weiqian Zhao (Matter and Radiation at Extremes, 2019)
A method based on the laser differential confocal principle is proposed for measurement of the uniformity of the inner and outer radius and shell thickness for an inertial confinement fusion (ICF) capsule. Firstly, this method uses the laser differential confocal measurement system (LDCS) driven by a precision air-bearing slide to scan and measure radially the outer radius, R, inner radius, r, and shell thickness, T, accurately. Secondly, a precision air-bearing rotation system is used to drive the capsule to rotate an angle, θ, in sequence, and the LDCS is used to measure R, r and T at the corresponding angle. Finally, the uniformity of the ICF capsule’s R, r and T can be calculated by the values of R, r and T measured at the position of each rotation angle. This method provides an approach for achieving high-precision, non-destructive, comprehensive, and rapid measurement of the uniformity of the inner and outer radius and shell thickness of an ICF capsule. Preliminary experiments indicate that measurement precision, using the proposed method for the uniformity of the outer radius, shell thickness and inner radius of the capsule, can reach 7.02 × 10−5, 5.87 × 10−4 and 6.52 × 10−5, respectively.